Reconstructing an African haploid genome from the 18th century. (February 2018) - Jagadeesan, Anuradha; Gunnarsdóttir, Ellen; Ebenesersdóttir, S.; Guðmundsdóttir, Valdis; Thordardottir, Elisabet; Einarsdóttir, Margrét; Jónsson, Hákon; Dugoujon, Jean-Michel; Fortes-Lima, Cesar; Migot-Nabias, Florence; Massougbodji, Achille; Bellis, Gil; et al.
Abstract A genome is a mosaic of chromosome fragments from ancestors who existed some arbitrary number of generations earlier. Here, we reconstruct the genome of Hans Jonatan (HJ), born in the Caribbean in 1784 to an enslaved African mother and European father. HJ migrated to Iceland in 1802, married and had two children. We genotyped 182 of his 788 descendants using single-nucleotide polymorphism (SNP) chips and whole-genome sequenced (WGS) 20 of them. Using these data, we reconstructed 38% of HJ's maternal genome and inferred that his mother was from the region spanned by Benin, Nigeria and Cameroon. Reconstructing the genome of an ancestor: 788 Icelanders are descended from a man who arrived there in 1802. 38% of his African mother's genome has now been reconstructed from their pedigree and the genomes and genotypes of current Icelanders up to 8 generations later.